2017
DOI: 10.1002/advs.201700379
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Electrocatalytic Conversion of Methane at Room Temperature

Abstract: Due to the greenhouse effect, enormous efforts are done for carbon dioxide reduction. By contrast, more attention should be paid for the methane oxidation and conversion, which can help the effective utilization of methane without emission. However, methane conversion and utilization under ambient conditions remains a challenge. Here, this study designs a Co3O4/ZrO2 nanocomposite for the electrochemical oxidation of methane gas using a carbonate electrolyte at room temperature. Co3O4 activated the highly effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
9

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 38 publications
1
69
0
9
Order By: Relevance
“…The high-energy MO sites are difficult to form thermochemically using O 2 (i.e., high G f ), but they can be generated by applying an anodic potential. [29] Ni(OH) 2 , [112] NiO/ ZrO 2 , [113,114] and Co 2 O 3 /ZrO 2 [115] have been explored as anode catalysts for methane activation at room temperature in carbonate electrolyte. The generation of methanol and higher alcohols such as propanol was observed by 1 H NMR or MS, but the TOF, TON, and Faradic efficiency were not qualified possibly due to the low yield.…”
Section: Electrocatalysts That Undergo Dehydrogenation Mechanismmentioning
confidence: 99%
“…The high-energy MO sites are difficult to form thermochemically using O 2 (i.e., high G f ), but they can be generated by applying an anodic potential. [29] Ni(OH) 2 , [112] NiO/ ZrO 2 , [113,114] and Co 2 O 3 /ZrO 2 [115] have been explored as anode catalysts for methane activation at room temperature in carbonate electrolyte. The generation of methanol and higher alcohols such as propanol was observed by 1 H NMR or MS, but the TOF, TON, and Faradic efficiency were not qualified possibly due to the low yield.…”
Section: Electrocatalysts That Undergo Dehydrogenation Mechanismmentioning
confidence: 99%
“…MeOH, HCHO, HCOOH Radical [108] NiO Radical [111] Pt/C, Pt/C-ATO, Pd/C, Pd/C-ATO incorporation of V 2 O 5 into TiO 2 /RuO 2 /PTFE GDE suppressed the formation of formaldehyde and formic acid, thereby increased MeOH selectivity. [108] A 5.6 wt% V 2 O 5 loading to the GDE increased the current efficiency of the electrode to 57% at 2.0 V versus SCE.…”
Section: Electrochemical Systems For Ch 4 Oxidationmentioning
confidence: 99%
“…It is interesting to note that, unlike OH − ions, CO 3 2− ions donate oxygen ions with successive release of CO 2 , which generated a large change in the enthalpy of reaction, favoring oxidation kinetics even at low temperatures. [111] Additionally, the presence of the redox couple Ni 2+ /Ni 3+ (by the reaction, Ni(OH) 2 + OH − ↔ NiOOH + H 2 O + e − ) at 0.5-0.6 V vs SCE favored the oxidation process. The products were identified as different oxygenates, such as methanol, ethanol, isopropanol, formaldehyde, formate, acetate, acetone, and carbon monoxide.…”
Section: Electrolyte Mediated Ch 4 Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Ma et al have reported that the electrochemical oxidation of methane in an electrolyzer can be used to produce higher alcohols such as propanol at room temperature. 14 Despite the demonstration of electrochemical oxidation of methane to methanol in previous reports, lack of consistency in the testing conditions and electrolytes used among the reports presents an additional challenge. A systematic study of the dependence of product distribution on applied potential, current, temperature, and pressure could facilitate the understanding of how various parameters affect the kinetics for methanol formation and aid in the advancement of this field.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%